The Hamster Cheek Pouch: An Experimental Model of Corneal Vascularization - Klintworth, Gordon K. (1973)
To gain insight into factors that might be responsible for the normal avascularity of the cornea and for its vascularization in certain pathologic states, an experimental model was designed in which corneal vascularization could be studied under controlled conditions in hamster cheek pouch chambers. Normal corneal tissue, as well as corneas that had been altered in a variety of ways (eg, boiled, autoclaved, freeze-thawed) were implanted into hamster cheek pouch chambers. The fate of the transplanted tissue was observed at regular intervals by direct visualization within the hamster cheek pouch at various magnifications and by light and electron microscopy. This report reviews observations on more than 300 such experiments. Normal and injured corneal autografts, allografts and xenografts and nonviable (autoclaved, boiled or freeze-thawed) corneas commonly became vascularized in the cheek pouch. When this occurred, a similar morphologic sequence of events preceded and accompanied the growth of blood vessels into the cornea. Vascular invasion was generally preceded by the formation of granulation tissue around the cornea. This was followed by a leukocytic, and frequently a fibroblastic, infiltration of the cornea. When cells did not invade the transplanted cornea, the cornea invariably remained avascular. In the present model, a swollen cornea was not a sufficient stimulus for corneal vascularization. The data suggest that under certain circumstances leukocytes may produce one or more factors which stimulate directional vascular growth. The findings are viewed in terms of current concepts on corneal vascularization.